Avaliação in vitro de um cimento de ionômero de vidro restaurador para colagem de bráquetes ortodônticos - Pimentel, Karine Almeida (2014)
Glass ionomer materials for bonding orthodontic brackets have advantages over composite resins such as easy of removal and lower risk of enamel damage, while maintaining the bond strength within the clinically ideal range (6.5 to 10 MPa). The ionomer material considered in the literature as the “gold standard” for bonding brackets (Fuji ORTHO LC) is hard to acquire and expensive to be used routinely. Therefore, this study aims at verifying the in vitro behavior of hybrid glass ionomer cement (GIC), indicated as restorative material (Vitro Fil LC), to be used as bonding material for orthodontic brackets. The sample was made up of 72 extracted bicuspids teeth divided into four groups and submitted to the same bonding procedures, except for the bonding materials. Vitro Fil LC GIC was handled in two different ways (VF1 group and VF2 group) and compared to Fuji ORTHO LC GIC (FO group) and to Transbond XT composite resin (XT group). The shear bond strength, adhesive remnant index (ARI), and the presence of enamel fracture after debonding were assessed. There was statistically significant difference among shear bond strength in the four groups: XT (15.9 + 4.3 MPa), FO (13.0 + 2.6 MPa), VF1 (10.1 + 1.9 MPa) and VF2 (5.1 + 2.7 MPa). ARI and the presence of enamel fracture was not statistically difference among three groups: XT, FO and VF1. Behavior of VF2 group in every test suggests that the type of handling employed for this group caused bonding failure in the enamel/adhesive interface, which precludes its clinical use. VF1 group showed bond strength within the clinically ideal range and its behavior following debonding was compatible to "gold standard" materials for bonding bracket, which suggests increased possibility of clinical use.